Nitrogen, Phosphorous, and Potassium Application Rate on the Young Seedling Growth of Salvadora persica - Fawzy F. Lasheen; Ahmed H. Negm; Soheir E. Hassan; Ehab Azab; Adil A. Gobouri; Mohammed Hewidy (Agriculture, 2021)
Salvadora persica is the most used medicinal shrub in the Arab world. This experiment was conducted to evaluate seedling performance at different rates of NPK. Seedlings were treated with N:P:K at 4:2:2 (N:P:K 2:2:2 g + 2 g of nitrogen supplemented as ammonium sulfate), 6:3:3 (N:P:K 3:3:3 g + 3 g of nitrogen supplemented as ammonium sulfate), 2:1:1S (N:P:K 1:1:1 g + 1 g of nitrogen supplemented as ammonium sulfate), 2:1:1U (N:P:K 1:1:1 g + 1 g of nitrogen supplemented as urea), 4:1:1S (N:P:K 1:1:1 g + 3 g of nitrogen supplemented as ammonium sulfate), 4:1:1U (N:P:K 1:1:1 g + 3 g of nitrogen supplemented as urea), 6:1:1S (N:P:K 1:1:1 g + 5 g of nitrogen supplemented as ammonium sulfate), 6:1:1U (N:P:K 1:1:1 g + 5 g of nitrogen supplemented as urea) in addition to the control. The results indicated that NPK application significantly affected the vegetative and root growth parameters and the chemical contents. Among the various treatments of NPK, the application of 6:3:3 rates showed the highest values for aboveground parts, root parameters, and greenness level. Therefore, the present study demonstrates the optimum NPK levels that can enhance seedling growth throughout the nursery period.